Use of Azospirillum baldaniorum cells in quercetin detection - Matvey Kanevskiy; Irina Kosheleva; Vladislav Menukhov; Elizaveta Zhdanova; Svetlana Borisova; Gennadiy Burygin; Svetlana Konnova; Viktor Bunin; Olga Guliy (International Association of Physical Chemists (IAPC), 2023)
The possibility of detection and determination of flavonoids by using microbial cells was shown for the first time using the quercetin - Azospirillum baldaniorum Sp245 model system. The activity of the flavonoids quercetin, rutin and naringenin toward A. baldaniorum Sp245 was evaluated. It was found that when the quercetin concentration ranged from 50 to 100 µM, the number of bacterial cells decreased. Rutin and naringenin did not affect bacterial numbers. Quercetin at 100 μM increased bacterial impedance by 60 %. Under the effect of quercetin, the magnitude of the electro-optical signal from cells decreased by 75 %, as compared with the no-quercetin control. Our data show the possibility of developing sensor-based systems for the detection and determination of flavonoids.